Who eats whom in the Barents Sea: a food web topology from plankton to whales: Ecological Archives E095‐124. Issue 5 (1st May 2014) - Planque, Benjamin; Primicerio, Raul; Michalsen, Kathrine; Aschan, Michaela; Certain, Grégoire; Dalpadado, Padmini; Gjøsæater, Harald; Hansen, Cecilie; Johannesen, Edda; Jørgensen, Lis Lindal; Kolsum, Ina; Kortsch, Susanne; et al.
Abstract : A food web is an ecological network and its topological description consists of the list of nodes, i.e., trophospecies, the list of links, i.e., trophic interactions, and the direction of interactions (who is the prey and who is the predator). Food web topologies are widely used in ecology to describe structural properties of communities or ecosystems. The selection of trophospecies and trophic interactions can be realized in different manners so that many different food webs may be constructed for the same community. In the Barents Sea, many simple food webs have been constructed. We present a comprehensive food web topology for the Barents Sea ecosystem, from plankton to marine mammals. The protocol used to compile the data set includes rules for the selection of taxa and for the selection and documentation of the trophic links. The resulting topology, which includes 244 taxa and 1589 trophic links, can serve as a basis for topological analyses, comparison with other marine ecosystems, or as a basis to build simulation models of the Barents Sea ecosystem. The data set consists of three related tables: (1) the list of taxa, (2) the list of pairwise interactions, and (3) the list of bibliographical references.